Single-molecule resolution of interfacial fibrinogen behavior: Effects of oligomer populations and surface chemistry - Kastantin, Mark (2011)
Using single-molecule total internal reflection fluorescence microscopy, the dynamic behavior of fibrinogen was observed at the interface between aqueous solution and various solid surfaces. Multiple populations of objects were observed, as characterized by surface residence times, interfacial diffusion, and fluorescence intensity. On all surfaces, populations exhibited direct links between surface residence time, rate of diffusion and fluorescence intensity. In particular longer-lived populations diffused more slowly and exhibited greater fluorescence intensity, leading to the conclusion that the objects represented fibrinogen monomers and discrete oligomer populations (dimers, trimers, etc.), and that these oligomer populations play an important role in the protein-surface interaction because of their long surface residence times. Two or three diffusive modes were observed for most populations, indicating that protein aggregates have multiple mechanisms for interaction with solid substrates. In addition, the fastest diffusive mode is believed to represent a hopping mode that often precedes desorption events. Surprisingly, a monolayer of PEG(5000) increased surface residence time and slowed diffusion of fibrinogen relative to bare fused silica or hydrophobically-modified fused silica, suggesting that the mechanism of PEG resistance to protein adhesion is more sophisticated than the simple repulsion of individual proteins.